Steam reduction of CO2 on Pd/TiO2 catalysts: a comparison between thermal and photocatalytic reactions. Issue 3 (31st October 2014) - Vaiano, V.; Sannino, D.; Ciambelli, P.
Abstract : The performances of Pd/TiO2 catalysts in the steam reduction of CO2 were analyzed in a photocatalytic and in a thermo-catalytic system. The comparison showed the superiority of the photocatalytic route. Abstract : The aim of this work was to compare traditional catalysis, which drives chemical reactions by thermal energy, with a photocatalytic process that can induce chemical reactions by light activation. Taking apart the obvious economic advantage to operate under mild conditions, a closer view of the characteristic behaviours of the thermal and light activation can give new insights for the selection of the more appropriate process. The performances of Pd/TiO2 catalysts in the steam reduction of CO2 were analyzed in a photocatalytic and in a thermo-catalytic system. The comparison in the range 140 °C–600 °C showed, for this reaction, the superiority of the photocatalytic route, since at any temperature level, no relevant products or higher selectivities towards the formation of methane and CO were observed. The CH4 photo-formation rate achieved a value of about 64 μmol g −1 h −1 at Pd loading equal to 1 wt%.